Nano-Engineered Cementitious Composites Principles and Practices - Han, Baoguo; Ding, Siqi; Wang, Jialiang; Ou, Jinping (Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on civil engineering materials and nanotechnology. Highlighting recent advances in the field of nano-engineered cementitious composites, it discusses their key principles, design and fabrication, testing and characterization, performance and mechanisms, as well as applications. Future developments and remaining challenges are also outlined. Nano-engineered cementitious composites are exceptionally strong, durable and offer multifunctional/smart performance that differs considerably from that of normal cementitious composites. Providing valuable insights into these composites' future development, the book offers an essential source of information, inspiration, theory and practical guidance for developing sustainable cementitious composites. As such, it will benefit researchers, scientists and engineers in the fields of civil engineering materials and nanotechnology alike. .